Circulating microRNAs Are Associated With Metabolic Markers in Adolescents With Hepatosteatosis - Lin, Haixia; Mercer, Kelly E.; Ou, Xiawei; Mansfield, Kori; Buchmann, Robert; Børsheim, Elisabet; Tas, Emir (Frontiers in Endocrinology, 2022)
Background: Altered hepatic microRNA (miRNA) expression may play a role in the development of insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD). Circulating miRNAs could mirror the liver metabolism. Objective. This study aimed to assess the relationship between serum miRNA profile in children with obesity, IR, and NAFLD. Methods. Adolescents with obesity (n = 31) were stratified based on insulin resistance and NAFLD status. One-hundred seventy-nine miRNAs were determined in the serum by quantitative RT-PCR. Differentially expressed miRNAs were compared between groups, and log-transformed levels correlated with metabolic markers and intrahepatic triglyceride. Results. Serum miR-21-5p, -22-3p, -150-5p, and -155-5p levels were higher in children with IR and NAFLD, and their expression levels correlated with hepatic fat and serum triglyceride. In patients with NAFLD, miR-155-5p correlated with ALT (r = 0.68, p<0.01) and AST (r = 0.64, p<0.01) and miR-21-5p and -22-3p levels correlated with plasma adiponectin (r = -0.71 and r = -0.75, respectively, p<0.05) and fibroblast growth factor-21 (r = -0.73 and r = -0.89, respectively, p<0.01). miR-27-3a level was higher in children without IR and NAFLD. Conclusions. Several miRNAs are differentially expressed in children with IR and NAFLD. Determining their mechanistic roles may provide newer diagnostic tools and therapeutic targets for pediatric NAFLD.